2021
DOI: 10.3389/fpsyg.2021.697045
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Feedback Practices, Student Feedback Motivation, and Feedback Behavior: How Are They Associated With Learning Outcomes?

Abstract: In spite of much recent theorizing about teacher provision of feedback, relatively fewer studies look at the dynamic relationships between teacher feedback practices, student feedback experience, and their learning outcomes in higher education settings. To fill this gap, this study looked at 308 university students' perceived teacher feedback practices and their feedback experiences in an English Studies course context at a key and non-key university, and explored how teacher feedback, student feedback motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
(104 reference statements)
2
9
0
Order By: Relevance
“…Student engagement has no doubt become an important issue in learning and teaching across different education institutions in recent decades (Kahu, 2013 ; Lim, 2017 ; Bao et al, 2021 ; Harris and Leeming, 2021 ; Rahimi and Zhang, in press ). Many studies have shown that student engagement is related to student satisfaction and experience, their learning outcomes and achievements (Pascarella and Terenzini, 2005 ; Carini et al, 2006 ; Lei et al, 2018 ; Teng and Zhang, 2018 , 2020 ; Gan et al, 2021 ). Despite the importance of engaging students in learning, it is a shared concern that, in practice, engaging students is difficult at almost all educational stages (Skinner and Belmont, 1993 ; Taylor and Parsons, 2011 ; Corso et al, 2013 ; Bundick et al, 2014 ; Farr-Wharton et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Student engagement has no doubt become an important issue in learning and teaching across different education institutions in recent decades (Kahu, 2013 ; Lim, 2017 ; Bao et al, 2021 ; Harris and Leeming, 2021 ; Rahimi and Zhang, in press ). Many studies have shown that student engagement is related to student satisfaction and experience, their learning outcomes and achievements (Pascarella and Terenzini, 2005 ; Carini et al, 2006 ; Lei et al, 2018 ; Teng and Zhang, 2018 , 2020 ; Gan et al, 2021 ). Despite the importance of engaging students in learning, it is a shared concern that, in practice, engaging students is difficult at almost all educational stages (Skinner and Belmont, 1993 ; Taylor and Parsons, 2011 ; Corso et al, 2013 ; Bundick et al, 2014 ; Farr-Wharton et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with the previous studies. For example, Gan et al (2021) investigated university students' perceived teacher feedback practices and their feedback experiences in an English studies course context. The results indicated that students reported a high level of teacher feedback use that motivated the students to learn.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Since the classroom is typically the most convenient and natural setting for giving and receiving responses, it is not surprising that these alternatives did not fare as well in the survey. Because learning is supposedly an apprenticeship and an internalization in which knowledge and abilities are transferred from the social to the cognitive plane, students spend most of class time in the midst of processing (Gan et al, 2021). It appears appropriate to provide feedback, even though some researchers have found that it can slow down students' ability to learn new material, especially when it is corrective.…”
Section: Discussionmentioning
confidence: 99%